To solve for f, we can simplify the equation step by step.
Starting with the given equation: 3(6-f) - 4 = 3f - 4
First, distribute the 3 to both terms inside the parentheses:
18 - 3f - 4 = 3f - 4
Next, combine like terms on both sides of the equation:
18 - 4 - 3f = 3f - 4
Simplify further by subtracting 18 and 4 from both sides:
-3f + 14 = 3f - 4
Now, we want to get all the f terms on one side of the equation and all the constant terms on the other side. We can do this by adding 3f to both sides:
-3f + 14 + 3f = 3f - 4 + 3f
Simplifying:
14 = 6f - 4
Next, isolate the variable f by adding 4 to both sides:
14 + 4 = 6f - 4 + 4
Simplifying further:
18 = 6f
Finally, solve for f by dividing both sides by 6:
18/6 = 6f/6
Simplifying the equation further:
3 = f
Therefore, the solution to the equation is f = 3.
Solve for f
3(6-f)-4=3f-4
1 answer